Construction and temporal behaviour study of multi RLC intense light pulses for dermatological applications. (18th August 2017) - Hamoudi, Walid K.; Ismail, Raid A.; Shakir, Hussein A.
ABSTRACT: Driving a flash lamp in an intense pulsed light system requires a high-voltage DC power supply, capacitive energy storage and a flash lamp triggering unit. Single, double, triple and quadruple-mesh discharge and triggering circuits were constructed to provide intense light pulses of variable energy and time durations. The system was treated as circuit in some cases and circuit in others with a light pulse profile following the temporal behaviour of the exciting current pulse. Distributing the energy delivered to one lamp onto a number of LC meshes permitted longer current pulses, and consequently increased the light pulse length. Positive results were obtained when using the system to treat skin wrinkles.